Diabetes knowledge and care practices among adults in rural Bangladesh: a cross-sectional survey. Issue 4 (23rd July 2018) - Fottrell, Edward; Ahmed, Naveed; Shaha, Sanjit Kumar; Jennings, Hannah; Kuddus, Abdul; Morrison, Joanna; Akter, Kohenour; Nahar, Badrun; Nahar, Tasmin; Haghparast-Bidgoli, Hassan; Khan, A K Azad; Costello, Anthony; et al.
Abstract : Background: Population knowledge of how to prevent, detect and control diabetes is critical to public health initiatives to tackle the disease. We undertook a cross-sectional survey of adults in rural Bangladesh to estimate knowledge and practices related to diabetes. Methods: In 96 villages in Faridpur district, trained fieldworkers surveyed 12 140 randomly selected men and women aged ≥30. They collected data on sociodemographic status, knowledge of diabetes and history of blood and urine glucose testing. Fasting and 2-hour post-glucose load capillary blood tests ascertained the diabetic status of respondents. Levels of knowledge and practices were analysed by sociodemographic characteristics and diabetic status. Results: The population showed low levels of diabetes knowledge overall, with only one in three adults able to report any valid causes of the disease. Knowledge of diabetes causes, symptoms, complications, prevention and control was significantly associated with age, education, wealth and employment. Only 14% of respondents reported ever having had a blood glucose test and strong associations with wealth were observed (least poor relative to most poor 2.91 (2.32–3.66)). 78.4% of known diabetics (ie, with a prior diagnosis) reported that they did not monitor their blood glucose levels on at least a monthly basis. However, they had better knowledge of the causes (odds relative to normoglycaemic individuals 1.62 (1.23–2.09)), symptoms (5.17 (3.41–7.82)), complications (5.18 (3.75–7.14)), prevention (4.18 (3.04–5.74)) and control (8.43 (4.83–14.71)). Conclusion: Knowledge of diabetes among rural adults in Faridpur is extremely poor. Levels of diabetes testing are low and monitoring of blood glucose among known diabetics infrequent. Diabetes prevention and control efforts in this population must include large-scale awareness initiatives which focus not only on high-risk individuals but the whole population. Trial registration number: ISRCTN 41083256 ; Pre-results.